Si Bagoes Sutami: The Transformation of Brantas’s CSR Begins from Sutami - Raden Sultani Indragunawan (Indonesian Journal of Social Responsibility Review (IJSRR), 2024)
The Corporate Social Responsibility (CSR) program of PT PLN NP UP Brantas is mostly of a charitable nature. This charity-based CSR program originates from proposals submitted by stakeholders or communities around the 13 hydropower plants managed by UP Brantas. This situation has resulted in UP Brantas lacking a sustainable, measurable, and broadly impactful CSR program for the community. Bagoes (Brantas Goes to School) is one of PLTA Sutami's educational CSR program that has the potential to become a sustainable program. Literature studies and interviews were conducted at SMK Brantas Karangkates to prepare the program as one of the sustainable education programs. This aligns with the 2024 CSR priority programs established by PT PLN NP, namely Education, Environment, UMK development, and CSV (Creating Shared Value). Based on the analysis conducted, Bagoes has transformed into Si Bagoes, Sustainable Improvement Brantas Goes to School. Si Bagoes, as the pilot project of PLTA Sutami's CSR program, will be implemented through various programs, namely Si Bagoes Sharing, Si Bagoes Class, EBT Si Bagoes, Si Bagoes Clean Water, and Si Bagoes Certification. Si Bagoes programs will be carried out by referring to the CSR management architecture of PLN NP and the governance of CSR UP Brantas.